Supporting students in professional socialisation: Guidelines for professional nurses and educators. (2017) - de Swardt, Hester Cathrina (Rina); van Rensburg, Gisela H.; Oosthuizen, M.J.
Highlights: Professional conduct in student nurses should be facilitated. Various teaching and facilitation strategies should be implemented. Gender and cultural awareness should be cultivated. Values and beliefs of the nursing are fundamental to professional socialisation. Abstract: Professional socialisation of nursing students involves learning skills, attitudes, behaviour and professional roles, largely in the clinical area. During clinical accompaniment and reflective discussions with a group of undergraduate Baccalaureate nursing students in South Africa, students reported negative professional socialisation experiences, primarily in the clinical area. Such experiences could influence the quality of patient care. The objective of this study was to develop and validate guidelines to support professional nurses and educators in the professional socialisation of student nurses. Evidence was generated from an exploration and description of the perceptions of professional nurses regarding their role in the professional socialisation of students, the perceptions of nurse educators regarding the teaching and facilitation of professional socialisation of students, and the socialisation experiences of students. Following a sequential mixed-methods design, qualitative data guided the collection of quantitative data. All data and literature directed the development of these guidelines, which experts reviewed and validated according to a set of criteria. These guidelines focus on the clinical, nursing educational institution environment and values and beliefs of the nursing profession. Facilitation of sound work ethics, professional behaviour, cultural and gender awareness, role modelling and the application of a range of teaching strategies is proposed.